Analysis on Private Practice Midwives Work Performance in the Implementation of Early Initation of Breastfeeding in Surabaya - Yefi Marliandiani; Atik Mawarni; Ani Margawati (Jurnal Manajemen Kesehatan Indonesia, 2014)
Keberhasilan pemberian ASI eksklusif dipengaruhi oleh inisiasi menyusu dini (IMD). di Surabaya pelaksanaan IMD hanya dilakukan pada 33% dari seluruh persalinan oleh bidan praktik swasta pada tahun 2009 dan menurun menjadi 27% pada tahun 2010. Berdasarkan survey pendahuluan didapatkan bahwa kinerja bidan praktik swasta (BPS) dalam pelaksanaan IMD belum optimal. Penelitian ini bertujuan untuk menganalisis kinerja bidan praktik swasta dalam pelaksanaan inisiasimenyusu dini di Surabaya. Jenis penelitian adalah observasional dengan pendekatan kualitatif. Informan penelitian adalah 10 BPS yang dipilih dari wilayah dengan cakupan IMD tersedikit dan terbanyak, masing-masing 5 orang. Informan triangulasi adalah sekretaris IBI Cabang Surabaya, asisten bidan dan ibu nifas. Data dikumpulkan dengan wawancara mendalam dan observasi terhadap pelaksanaan IMD. Pengolahan metode content analysis. Hasil penelitian menunjukkan 6 dari 10 BPS sudah melaksanakan IMD tetapi dengan cara yang tidak tepat. Dilihat dari kemampuan kognitif semua responden tentang IMD masih kurang. Enam dari 10 BPS bersikap positif tentang IMD. Motivasi BPS untuk melaksanakan IMD dipengaruhi oleh manfaat IMD, himbauan dinas kesehatan dan IBI serta permintaan pasien. Semua responden mengatakan tidak pernah disupervisi oleh bidan koordinator (bikor) walaupun responden membutuhkan supervisi. Dapat disimpulkan bahwa kinerja BPS dalam pelaksanaan IMD belum optimal karena kemampuan kognitif masih kurang serta tidak adanya supervisi dari bikor Successfulness of an exclusive breastfeeding was influenced by early breastfeeding initiation (IMD). In Surabaya, implementation of IMD was only done by 33% of all deliveries assisted by private practice midwives in 2009, and it decreased to 27% in 2010. Based on a preliminary study, work performance of private practice midwives (BPS) in the implementation of IMD was not optimal. Objective of this study was to analyze work performance of private practice midwives in the implementation of early breastfeeding initiation in Surabaya. This was an observational-qualitative study. Study main informants were 10 BPS who were selected from area with the lowest and highest IMD coverage; each of area consisted of 5 BPS. Triangulation informants were a secretary of IBI Surabaya branch, midwives assistance, and post-delivery mothers. Data were collected through in-depth interview and observation on the implementation of IMD. Data were managed and analyzed by applying content analysis method. Results of the study showed that six out of 10 BPS had implemented IMD though with improper way. Cognitive ability of all respondents regarding IMD was still inadequate. Six out of 10 BPS had positive attitude toward IMD. Motivation of BPS to implement IMD was influenced by IMD benefits, suggestion from district health office and from IBI, and from patient’s request. All respondents told that no supervision by coordinator midwives was conducted although it was needed by respondents. In conclusion, work performance of BPS in the implementation of IMD was not optimal. It was caused by inadequate cognitive ability of BPS, and no supervision from a coordinator midwives.